Comparison of strategic content of facilities managers functions with other building support practitioners in Lagos, Nigeria. Issue 2 (16th April 2018) - Koleoso, Hikmot Adunola; Omirin, Modupe Moronke; Adejumo, Femi
Abstract : Purpose: The literature propounds that facilities management (FM) differs from other building support services (BSS) because it features a significant strategic content. However, research indicates that this deep seated strategic and value-adding practice is mostly unavailable except in the most matured markets. The purpose of this paper is to compare the strategic content of the functions performed by FM practitioners with that of other BSS providers in Lagos, the commercial hub of Nigeria. This is to determine if the content of the FM functions is comparatively more strategic and invariably more value-adding than that of other BSS providers as indicated in literature and also to identify required areas of improvement, both for practice and training. Design/methodology/approach: A survey was carried out through self-administered questionnaire directed to a sample of 123 BSS providers that work with office buildings in Lagos, Nigeria. The data collected were analyzed using frequency counts, means, χ 2 test and Wilcoxon signed rank test. Findings: Rather than the strategic tasks, the FM group as with the non-FM group were more regularly involved with the less specialized facilities operations/maintenance and facilities support service tasks such as, security, fire, emergency management, cleaning and waste management. Specialized FM support service tasks such as mail services, reprographics, catering and travel services, were least often performed by both groups. The study found that facilities managers were slightly more involved than the non-facilities managers in performing the strategic group of tasks. This was indicated by the higher cumulative mean values and ranking of the level of involvement. The facilities managers also ranked higher in their involvement in the individual strategic tasks. The study also shows that FM practitioners use the more strategic ways to determine the needs of users. These findings imply that FM presents a slightly more strategic edge, which is, however, insufficient. Practical implications: Although the FM practitioners may feature a slightly more strategic content of functions than their non-FM counterparts, the edge is insufficient to add significant value to clients' business as postulated in literature. Lagos FM practitioners must become more involved in strategic functions in order to enhance FM's value-adding edge and hence distinguish it better from other BSS practices. Originality/value: The study positions the Nigerian FM practice in the light of expectations in literature and re-affirms the supposition that the practice is relatively strategically immature. It also identifies the contingent needs of local and multinational organizations that may require or intend to provide FM and other BSS in the Nigerian context, invariably allowing for international comparisons.